PEMEROLEHAN BAHASA KEDUA ANAK TK NEGERI PEMBINA USIA 4 TAHUN - Hasan Suaedi* (Universitas Muhammadiyah Jember, 2016)
Second language acquisition (SLA) is one of the formal studies in language learning which is different from the first language acquisition (FLA). In FLA, a child, unconsciously learn language from his closest person; father or mother. SLA. At TK Negeri Pembina, SLA occurs in formal learning activities through many different ways; i.e., telling stories, drawing, and playing. In this study, the writer applied qualitative method. It aims at giving clear description on the talks occur during the learning process. The results of the study show that (1) The language production of 4 year old children at TK Negeri Pembina comprises six parts of speech: (a) nouns, (b) verbs, (c) adverb, (d) pronouns, (e) adjectives, and (f) numbers. And nouns are the most frequently used. (2) In sentence case, the language production is mostly in interrogative sentences when teacher and students are having questions and answer during the learning process and (3) The use of pronouns are appropriate with its functions. The 4 year old children can distinguish the use of pronouns; personal, singular and also plural pronouns.Key words: Second Language Acquisition (SLA), words, sentence, pronouns